THE IMPLEMENTATION OF INQUIRY LEARNING ON STUDENTS' LEARNING OUTCOMES AND CRITICAL THINKING SKILLS IN THE DIGESTIVE SYSTEM MATERIAL - Nurlaili Nurlaili; Ruqiah Ganda Putri Panjaitan; Laili Fitri Yeni (JURNAL PENA SAINS, 2021)
This research is aimed to determine the students’ achievement and critical thinking on the digestion system topic. This study was conducted using a quasi-experiment with a control group pre-test and post-test design. Furthermore, the samples were chosen using the purposive sampling technique. The instrument consisted of 20 multiple-choice tests. Findings indicate that the average student achievement is 16.71 in the experiment and 12.92 in the control class. The t-test also can be known as t-count t-table (1.71 1.68), which means a significant difference between experiment average and control average. Based on the test result in the experiment class, it can be assumed that there is an enhancement of the average percentage of students' critical thinking from 63% to 84%. Thus, it can be concluded that inquiry learning model can increase the students’ achievement and critical thinking.